Tutoring system for fraction using siemer’s & angelides its architecture - Hong, Peck Hui (2013)
The research discusses on the providing web-based learning for students in tutoring system so that students can access the proposed tutoring system via internet. The aim of the proposed tutoring system is to provide appropriate content of the Mathematics notes in Topic “Pecahan” to the Year 6 students in primary school. The content of notes will be using Bahasa Malaysia as medium language. The TS for Y6Maths is an alternative way of studyMathematics that makes students have fun and more understanding in learning process. The tutoring system is allowed students learn Mathematics in a suitable environment at any time and place. When students answer assessment, the system will record their results in the report card where parents and teachers are able to monitor their study progress. The concept and architectural parts of the proposed tutoring system are defined and discussed in this paper. The proposed tutoring system will be implemented in PHP script language and HTML pages based on Siemer’s & Angelides ITS Architecture which is the three-tiered architecture, it consists of three main models such as Domain Model, Tutoring Model and User Model. these models are controlled by overall system control. The overall system control is acted as a controller or handler to handle data between interfaces and database.